User Satisfaction with Shopee Chatbot:: An Extended TAM with Perceived Convenience as an Intervening Variable - Nita Nita; Ratna Roostika (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the effect of the Technology Acceptance Model (TAM) on user satisfaction, with perceived enjoyment serving as a mediating variable. The population of this study consists of all Shopee users in Indonesia who have interacted with the Shopee Chatbot. The sample includes Shopee users who have had experience interacting with the Shopee Chatbot. The research data were analyzed using SmartPLS. The results indicate that perceived usefulness (PU) has a positive and significant effect on user satisfaction, while perceived ease of use (PEOU) shows a positive effect but is not statistically significant. Perceived enjoyment (PE) also has a positive and significant influence on user satisfaction. In addition, perceived usefulness and perceived ease of use have positive and significant effects on perceived enjoyment. Furthermore, this study reveals that perceived enjoyment, as a mediating variable, successfully mediates the relationship between the Technology Acceptance Model and user satisfaction.